Performance of bentonite and vermiculite mixtures as grounding enhancement materials - Wan Ahmad, W. F. H.; Jasni, J.; Krishnan, P.; Ab-Kadir, M. Z. A. (IEEE, 2023)
Grounding means connecting an electrical circuit or device to the ground. During lightning, high voltage could be developed in the electrical distribution system wires. Therefore, grounding system provides a safe return path around the electrical system and minimizes damage from such occurrences. A good grounding system has very low resistance value. Low earth resistance will ensure that any high fault current will be directed into ground due to low resistive path presented. Earth resistance varies with certain soil specifications, i.e. moisture, salt content, temperature, types and compactness. Note that in this study, soil is treated using natural enhancement material in order to improvise its moisture retaining capability. Four grounding systems with copper conductors were installed with NEM mixtures for their performances to be contrasted with a Reference grounding system with no NEM added to the vicinity of the ground conductor. The selected NEMs were Bentonite and Vermiculite with different ratios, i.e. 100% Bentonite, 100% Vermiculite, Bentonite and Vermiculite Mix A, and Bentonite and Vermiculite Mix B. Note that all five grounding systems were installed near to SGS, UPM with their daily earth resistance measurements were done for more than 100 days, i.e. from 1st Feb 2019 until 22nd May 2019. By applying 0° separation angle and 62% method, the average earth resistance value was obtained, and the best performed grounding system installation in descending order were identified to be Bentonite and Vermiculite Mix A, 100% Bentonite, Bentonite and Vermiculite Mix B, and 100% Vermiculite with their measured earth resistance values were demonstrated to be 28.06%, 32.54%, 58.89%, and 103.95%, respectively compared to the earth resistance value of the Reference grounding system on day-0. Thus, 100% Vermiculite may not be suitable to be used as NEM in grounding system but Bentonite and Vermiculite Mix A could be said to be better and comparable to Bentonite which could be proposed as a new grounding enhancement mixture. Note that Bentonite ratio was more in Mix A compared to Mix B.